Evolution of microstructure and deformation resistance in creep of tempered martensitic 9-12%Cr-2%W-5%Co steels - Agamennone, Roberto; Blum, Wolfgang; Gupta, Chiradeep; Chakravartty, Jayanta K. (Acta Materialia, 2006)
The microstructural evolution during creep at 923 K of four tempered martensite 9-12%Cr-steels modified with 2%W and 5%Co was quantified by electron microscopy. Coarsening of subgrains with strain towards the stress dependent steady state was confirmed. The evolution of the precipitate structure is similar with regard to M23C6 (M: metallic element, X: N, C) and Laves phase (Fe,Cr)2(W,Mo) but differs strongly with regard to V-bearing precipitates. Low temper temperatures promote precipitation of V as M2X instead of VX. This appears to be critical in causing anomalously fast breakdown of initially high creep resistance. Dissolution of small V-bearing precipitates and corresponding loss of precipitation hardening in the subgrain interior is proposed to be the reason for this breakdown. The dissolution is caused by fast coarsening of M2X precipitates and precipitation of Z-phase at subgrain boundaries. Large M2X precipitates at subgrain boundaries are proposed to be nucleation sites of Z-phase. © 2006 Acta Materialia Inc.
Created from Fastlane, Scopus look-up
Keywords: Creep; Precipitates; Subgrains; Tempered martensite steels; Z-phase